Influence of liquid properties on atomization characteristics of flow-blurring injector at ultra-low flow rates. (15th March 2019) - Khan, Mohammed Asad; Gadgil, Hrishikesh; Kumar, Sudarshan
Abstract: Atomization and efficient evaporation at extremely small flow rates is an additional challenge for liquid fueled small-scale combustor and burner applications. In the present study, experiments are conducted to investigate the effects of liquid properties on atomization of flow-blurring atomizer at ultra-low liquid flow rate (2.78–41.7 μL/s). Shadowgraphy, backlight imaging technique and laser based spray visualization methodology were employed for atomization characterization. Formation of three different atomization regimes namely bubble bursting, weak spray and fully developed spray was observed with a gradual increase in airflow rate (8.33–83.3 mL/s). Prompt mode of atomization in weak spray regime produces coarse droplets, while a sudden reduction in droplet size is observed in fully developed spray regime. Fine atomization in fully developed spray regime is attributed to flow-blurring effect due to air recirculation and thereby formation of highly turbulent two-phase flow inside the injector. This investigation reports that the criterion proposed in literature is not sufficient to achieve enhanced atomization through flow-blurring phenomenon. Experiments demonstrate that viscosity has marginal effect on atomization, however, surface tension dominates the atomization characteristics in a flow-blurring atomizer. Meanwhile, Weber number appears an appropriate parameter to predict the atomization regime transition. Graphical abstract: Image 1 Highlights: Detailed study of flow-blurring atomizer is presented for ultra-low flow rates. Internal two-phase flow structure result in formation of three atomization regime. Atomization with flow-blurring phenomenon observed above the critical Weber number.